Mixed Neighbourhoods: Effects of urban restructuring and new housing development - Boschman, Sanne; Bolt, Gideon; van Kempen, Ronald; van Dam, Frank (A+BE | Architecture and the Built Environment, 2015)
Many European countries use mixed housing policies to decrease the spatial concentration of low-income households. Also in the Netherlands, social housing in deprived neighbourhoods is demolished and replaced by more expensive dwellings. The idea is that these new dwellings attract higher-income groups to urban restructuring neighbourhoods. At the same time, however, also large numbers of relatively expensive dwellings have been built at greenfield locations. This leads to a dilemma: will higher-income households choose for housing in deprived neighbourhoods, while also attractive new housing on greenfield locations is available? This study shows that urban restructuring attracts higher-income households to mixed tenure developments in deprived neighbourhoods, even when competing with greenfield development. Nevertheless, another process is also taking place: especially in urban regions with extensive greenfield development, there is a significant outflow of higher-income households from deprived neighbourhoods. The net result is an increasing concentration of low-income households in deprived neighbourhoods.